When and how did the terrestrial mid-Permian mass extinction occur? Evidence from the tetrapod record of the Karoo Basin, South Africa - Day, Michael O. (Proc Biol Sci, 2015)
A mid-Permian (Guadalupian epoch) extinction event at approximately 260 Ma has been mooted for two decades. This is based primarily on invertebrate biostratigraphy of Guadalupian–Lopingian marine carbonate platforms in southern China, which are temporally constrained by correlation to the associated Emeishan Large Igneous Province (LIP). Despite attempts to identify a similar biodiversity crisis in the terrestrial realm, the low resolution of mid-Permian tetrapod biostratigraphy and a lack of robust geochronological constraints have until now hampered both the correlation and quantification of terrestrial extinctions. Here we present an extensive compilation of tetrapod-stratigraphic data analysed by the constrained optimization (CONOP) algorithm that reveals a significant extinction event among tetrapods within the lower Beaufort Group of the Karoo Basin, South Africa, in the latest Capitanian. Our fossil dataset reveals a 74–80% loss of generic richness between the upper Tapinocephalus Assemblage Zone (AZ) and the mid-Pristerognathus AZ that is temporally constrained by a U–Pb zircon date (CA-TIMS method) of 260.259 ± 0.081 Ma from a tuff near the top of the Tapinocephalus AZ. This strengthens the biochronology of the Permian Beaufort Group and supports the existence of a mid-Permian mass extinction event on land near the end of the Guadalupian. Our results permit a temporal association between the extinction of dinocephalian therapsids and the LIP volcanism at Emeishan, as well as the marine end-Guadalupian extinctions.